Melatih Kemampuan Berpikir Kritis Siswa Melalui Model Inkuiri untuk Meminimalisir Miskonsepsi IPA - Julianto; Fitria Hidayati; Julia Fatimatur Rahmawati; Rizka Cahyaningsih; Irvan Surrahman (Postgraduate, University of Mataram, 2023)
This research was conducted using the literature review method with the aim of evaluating and integrating relevant previous research by training students' critical thinking skills through an inquiry model in order to minimize science misconceptions. The results of the literature review show that the inquiry model is one of the most effective learning models for training students' critical thinking skills and minimizing science misconceptions. The inquiry model emphasizes students' own discovery by inviting students to observe; ask; gather; and communicate their findings. Previous research also shows that training students' critical thinking skills can be done through various approaches and strategies, such as using open questions in group discussions; the use of diverse resources; and the use of technology. Besides that; Science misconceptions can be minimized by inviting students to actively participate in learning, such as providing constructive feedback and providing authentic direct experience. From the results of the literature review, we conclude that training students' critical thinking skills through inquiry models can be a solution to minimize the occurrence of science misconceptions. Therefore, implementing the inquiry model in science learning can increase students' understanding of science concepts and also improve their critical thinking skills.